Infinitesimal Rigidity Analysis of a Bar-Joint Framework With Connected Braced Triangles (European Journal of Pure and Applied Mathematics, 2024)
The aim of this paper is to provide detailed infinitesimal rigidity analysis of a planar infinite bar-joint framework consisting of connected braced triangles. This is achieved in a purely mathematical manner, using the infinitesimal flex condition, as we identify the non trivial infinitesimal flexes of the finite framework consisting of $n$ connected triangles. The result is then generalized to the infinite case leading to the identification of a base for the space of all infinitesimal flexes.